2000
DOI: 10.1074/jbc.275.2.906
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Rhodospirillum rubrumF0F1 ATP Synthases Containing Spinach Chloroplast F1 β or α and β Subunits Reveal the Essential Role of the α Subunit in ATP Synthesis and Tentoxin Sensitivity

Abstract: Trace amounts (ϳ5%) of the chloroplast ␣ subunit were found to be absolutely required for effective restoration of catalytic function to LiCl-treated chromatophores of Rhodospirillum rubrum with the chloroplast ␤ subunit (Avital, S., and Gromet-Elhanan, Z. (1991) J. Biol. Chem. 266, 7067-7072). To clarify the role of the ␣ subunit in the rebinding of ␤, restoration of catalytic function, and conferral of sensitivity to the chloroplastspecific inhibitor tentoxin, LiCl-treated chromatophores were analyzed by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Furthermore, the close distance of the side chain NH group of ␣Arg-297 and the main chain carbonyl of L-MeAla-1 (3.2 Å) suggests additional hydrogen bonding between the inhibitor and the ␣-subunit, although this contact was not indicated by HBPLUS (28). The importance of correct hydrogen bonding for the positioning of the inhibitor in the binding cleft is supported by biochemical and mutagenesis studies that demonstrated that tentoxin binding fails in ␤Asp-833Glu mutants or in species that naturally contain glutamate in the position of the essential ␤Asp-83 (7,8). Tentoxin resistance might simply result from the changed orientation of the carboxyl group in the binding cleft, which affects the correct hydrogen bonding and the alignment of the inhibitor.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, the close distance of the side chain NH group of ␣Arg-297 and the main chain carbonyl of L-MeAla-1 (3.2 Å) suggests additional hydrogen bonding between the inhibitor and the ␣-subunit, although this contact was not indicated by HBPLUS (28). The importance of correct hydrogen bonding for the positioning of the inhibitor in the binding cleft is supported by biochemical and mutagenesis studies that demonstrated that tentoxin binding fails in ␤Asp-833Glu mutants or in species that naturally contain glutamate in the position of the essential ␤Asp-83 (7,8). Tentoxin resistance might simply result from the changed orientation of the carboxyl group in the binding cleft, which affects the correct hydrogen bonding and the alignment of the inhibitor.…”
Section: Resultsmentioning
confidence: 59%
“…Analysis of tentoxin-sensitive and -resistant Nicotiana species indicated that residue ␤Asp-83 located at the interface of the N-terminal ␤-barrel domains in the ␣-and ␤-subunits is crucial for tentoxin binding and͞or sensitivity (7). Substitution of this residue by glutamate, alanine, or leucine caused tentoxin resistance (8), whereas substitution of the native glutamate in the tentoxin-resistant Chlamydomonas reinhardtii F 1 -ATPase by aspartate induced tentoxin sensitivity (9). On the other hand, tentoxin-resistant F 1 -ATPases from thermophilic Bacillus PS3 and from E. coli (10) contain aspartate in the equivalent position of the ␤-subunit as well.…”
mentioning
confidence: 99%
“…An additional distinction has been made based on previous studies which have examined tentoxin sensitivity of hybrid enzymes containing the subunit from tentoxin-sensitive chloroplasts. The F 1 enzymes which are normally tentoxin resistant either became tentoxin sensitive (SC) or remained insensitive to tentoxin (RC) when the CF 1 was present (19,21,23). Heavy lines have been drawn above two segments of residues which were used to create chimeric R subunits.…”
Section: Methodsmentioning
confidence: 99%
“…CF 1 lacking the δ and subunit, R C 3 C 3 γ C , was reconstituted from native R and subunits and recombinant, refolded γ subunit as previously described (22,25). C (26), D83L (23), and γ C (25) were expressed as inclusion bodies in E. coli BL21(DE3)/pLysS cells grown to steady state at 37°C. ATP (grade II) and tentoxin were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation